The generalization of ratio-cum product estimator for the arbitrary sample design - Bartkus, Ignas; Plikusas, Aleksandras (Lietuvos matematikos rinkinys, 2009)
The generalization of a dual to ratio-cum-product estimator of the finite population total for the arbitrary sample design is given. The approximate variance is calculated and variance estimator is constructed. Some simulation results are presented for the comparison of ratio-cum-product estimator with some known estimators.